Psychometric analysis of a scale of emotional dependence in peruvian college students [Análisis psicométrico de una escala de dependencia emocional en universitarios peruanos] - Ventura, José (2016)
ABSTRACT The present article analyzes the psychometric properties of the Emotional Dependence Scale, developed by Lemos Hoyos and Londoño Arredondo (2006), composed by 23 items, with six Likert type response alternatives. A total of 520 students (147 males and 373 females) participated in the study, ranging in age from 16 to 47 years old, with an average of 22.28 years. The participants were divided into a sample of 200 people for the exploratory factor analysis and 320, for confirmatory factor analysis. The analysis of the item-test correlation indicated a suitable homogeneity of the items. The reliability was analyzed by means of the coefficient omega, varying according to the models, from .85 to .93. Exploratory factor analysis suggested the existence of a single factor. Due to the difference with the original version, confirmatory factor analysis was performed, concluding that a general factor model with six specific factors has acceptable values of goodness of fit, but does not have good reliability values for the sample under study.